(untitled) (Revista Brasileira Multidisciplinar, 2021)
Poultry parasitosis are old problems, but they can still cause several impasses to poultry production in its various breeding systems. Thus, this study aimed to evaluate the prevalence of the main helminths in chickens under different rearing systems through a literature review from 2011-2020. In general, helminths showed a prevalence of 63,1 % in poultry flocks, and the rearing system interferes with the frequency of parasitosis, being noticeably lower for intensive farming than for semi-intensive and extensive or backyard. The most prevalent nematodes were Heterakis gallinarum, Ascaridia galli and Capillaria spp, with frequencies varying according to the production system, in which, in the intensive system, nematodes involving intermediate hosts were less prevalent, with A. galli being the most frequent. In relation to the cestodes Raillietina spp., Hymenolepis sp. and Choanotaenia infundibulum, these were the most prevalent in descending order regardless of the production system adopted. While trematodes were rarely reported in studies. This study reinforces bird care by maintaining a deworming schedule, in addition to reinforcing biosafety measures aimed at breaking the parasite cycle.